Early‐onset absence epilepsy: SLC2A1 gene analysis and treatment evolution. Issue 5 (30th September 2012) - Agostinelli, S.; Traverso, M.; Accorsi, P.; Beccaria, F.; Belcastro, V.; Capovilla, G.; Cappanera, S.; Coppola, A.; Dalla Bernardina, B.; Darra, F.; Ferretti, M.; Elia, M.; et al.
<x xml:space="preserve">Abstract</x> Background and purposes To determine the prevalence of SLC2A1 mutations in children with early‐onset absence epilepsy (EOAE) and to investigate whether there were differences in demographic and electroclinical data between patients who became seizure‐free with anti‐epileptic drug (AED) monotherapy (group I) and those who needed add‐on treatment of a second AED (group II). Methods We reviewed children with EOAE attending different Italian epilepsy centers. All participants had onset of absence seizures within the first 3 years of life but otherwise conformed to a strict definition of childhood absence epilepsy. Mutation analysis of SLC2A1 was performed in each patient. Results Eighty‐four children (57 in group I, 27 in group II) fulfilled the inclusion criteria. No mutation in SLC2A1 was found. There were no statistical differences between the two groups with regard to F/M ratio, age at onset of EOAE, early history of febrile seizures, first‐degree family history for genetic generalized epilepsy, duration of AED therapy at 3 years after enrollment, use of AEDs at 3 years, failed withdrawals at 3 years, terminal remission of EOAE at 3 years, and 6‐month follow‐up EEG data. Mean duration of seizures/active epilepsy was significantly shorter in group I than in group II (P = 0.008). Conclusions We demonstrate that in a large series of children with rigorous diagnosis of EOAE, no mutations in SLC2A1 gene are detected. Except for duration of seizures/active epilepsy, no significant differences in demographic and electroclinical aspects are observed between children with EOAE who responded well to AED monotherapy and those who became seizure‐free with add‐on treatment of a second AED.